Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5489/cuaj.1195
|View full text |Cite
|
Sign up to set email alerts
|

Histologic variants of urothelial bladder cancer and nonurothelial histology in bladder cancer

Abstract: Bladder cancer can be classified histologically as urothelial or non-urothelial. Urothelial cancer has a propensity for divergent differentiation, which has increasingly been recognized in recent years due to heightened awareness and improved immunohistochemistry techniques. Furthermore, the recent World Health Organization classification of urothelial cancers improved clarity on this issue, with its listing of 13 histologic variants of urothelial cancer. The divergent differentiation patterns include, amongst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 62 publications
(75 reference statements)
7
122
0
3
Order By: Relevance
“…It has been hypothesized that the difference in prognosis may be due to resistance of tumors with glandular differentiation to chemotherapies directed at usual urothelial carcinoma-however, data supporting this hypothesis are lacking. In contrast, other studies 23,24 have suggested that glandular differentiation does not affect prognosis after adjusting for pathologic stage. Despite these controversies, it is recommended that divergent differentiation within a urothelial carcinoma should be documented in surgical pathology reports.…”
Section: Primary Glandular Maligancies Of the Bladdermentioning
confidence: 76%
“…It has been hypothesized that the difference in prognosis may be due to resistance of tumors with glandular differentiation to chemotherapies directed at usual urothelial carcinoma-however, data supporting this hypothesis are lacking. In contrast, other studies 23,24 have suggested that glandular differentiation does not affect prognosis after adjusting for pathologic stage. Despite these controversies, it is recommended that divergent differentiation within a urothelial carcinoma should be documented in surgical pathology reports.…”
Section: Primary Glandular Maligancies Of the Bladdermentioning
confidence: 76%
“…To our knowledge, no published articles have focused on treatment guidelines for sarcomatoid variant of urothelial carcinoma according to stage, although one group suggested that radical cystectomy rather than intravesical therapy should be the preferred option of treatment for patients with stage T1 disease. 9,10 Overall, prognosis of sarcomatoid carcinoma is poor, with a five-year survival of 20.3% after radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…UC is known to show variant histologic features otherwise known also as divergent differentiation, with estimates ranging from 7% to 81% in series reporting differentiation patterns ofUCs (6,7).…”
Section: Urothelial Carcinoma Variantsmentioning
confidence: 99%